Yorkshire Ditties, Second Series : To which is added The Cream of Wit and Humour from his Popular Writings - Hartley, John, 1839-1915 (Salt Lake City, UT : Project Gutenberg, 2006)
"Yorkshire Ditties, Second Series" by John Hartley is a collection of poetry written in the late 19th century. The book features a variety of humorous and heartfelt verses that celebrate Yorkshire culture and working-class life, often embracing the dialect and experiences of the region's inhabitants. It serves as both a social commentary and a tribute to the resilience and wit of ordinary people, capturing their joys, sorrows, and everyday struggles. The opening of "Yorkshire Ditties, Second Series" introduces the reader to a world steeped in local charm and character. It begins with a dedication and a preface that expresses the author's hope that readers will appreciate the homegrown dialect and themes. The first poem, "Th' Better Part," features a conversation between a young man and an elderly figure, exploring themes of contentment and the relativity of wealth. The old man reflects on the burdens of riches compared to the peace that comes from a clear conscience and modest living, emphasizing a life governed by integrity and satisfaction in simple pleasures. This sets the tone for the subsequent poems, which promise a blend of humor, wisdom, and nostalgia for a bygone era. (This is an automatically generated summary.)
Th' Better Part -- Done Agean -- Latter Wit -- My Gronfayther's Days -- Heart Brocken -- To a Daisy -- A Bad Sooart -- All we Had -- Give it 'em Hot -- Th' Honest Hard Worker -- Niver Heed -- Sing On -- What aw Want -- What it is to be Mother -- What is It -- Come thi Ways! -- Advice to Jenny -- Ther's mich Expected -- A Strange Stooary -- Take Heart -- Did yo Iver -- An Old Man's Christmas Morning -- Billy Bumble's Bargain -- Moral -- Rejected -- Duffin Johnie -- Lost Love -- Th' Traitle Sop -- To Let -- Fault Finders -- Disapointment -- Work Away -- New Machinery &c -- September Month -- A Hawporth -- Buttermilk &c -- It's a comfort -- Progress -- Try Again -- Jealousy -- Winter -- Persevere -- Booith-Taan Election -- Election -- None think Alike -- Seaside
Release date is 2006-02-19
Produced by David Fawthrop
Keywords: Dialect poetry, English -- England -- Yorkshire; Yorkshire (England) -- Poetry; Poetry of places